Barbenigma Powell & Miller, a bizarre new genus and two new species of scale insects (Hemiptera: Coccomorpha: Ortheziidae) from the United States - Powell, Erin C.; Miller, Douglass R.; Keller, Oliver (Zootaxa, 2024)
A strange new genus and two species of scale insect from the United States, Barbenigma Powell & Miller, gen. nov. and Barbenigma biza Powell & Miller, sp. nov. and B. boscus Powell & Miller, sp. nov. (Hemiptera: Coccomorpha: Ortheziidae) are described and illustrated, including the adult female and immature stages available. Barbenigma boscus was recently collected in Nebraska on the roots of grasses; B. biza is described from a series of undetermined specimens from Florida found in the Florida State Collection of Arthropods. These species, which have three-segmented antennae, no wax plates, conspicuous clusters of quadrilocular ducts on the abdomen, thoracic and abdominal spiracles set in a ring of pores, legs reduced in size, sparse ornate fimbriate dorsal setae, and very few capitate spines, stretch our current concept of the family Ortheziidae. The anal ring morphology, a fused trochanter and femur, presence of abdominal spiracles, large differentiated setae on the apex and subapex of the terminal segment of the antenna, a reduced number of ventral abdominal segments, and the presence of modified quadrilocular pores (most likely homologous to the ovisac band), support placement in Ortheziidae. We provide an updated phylogenetic analysis of Ortheziidae based on morphological characters with the new species included. The analysis demonstrates that the four species previously placed in the family Carayonemidae and the two new species of Barbenigma form a monophyletic group that should be placed within the Ortheziidae as the subfamily Carayoneminae Richard new synonymy and change of rank. The tribes Carayonemini Richard and Barbenigmini Powell & Miller tribe nov. are proposed as subunits within the subfamily. A revised key to the world species of Carayoneminae is provided.